2009
DOI: 10.1111/j.1574-6968.2009.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding hemagglutinin (HBHA) ofMycobacterium lepraeis expressed during infection and enhances bacterial adherence to epithelial cells

Abstract: A heparin-binding hemagglutinin (HBHA) expressed on the surface of Mycobacterium tuberculosis is an antigenic protein that has been implicated in bacterial adherence to epithelial cells and systemic dissemination. In this study, the potential role of the Mycobacterium leprae HBHA (ML-HBHA) homologue in leprosy was investigated. Initially, the in vivo expression of HBHA and its association with the M. leprae cell envelope was confirmed by immunoblotting and proteomic analysis. Mycobacterium leprae recombinant H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Hlp and HBHA are well known as extracellular matrixbinding proteins. While HBHA binds heparan sulfate (13,20), Hlp has been described as a multifunctional adhesin able to interact with laminin, hyaluronic acid, heparan sulfate, and collagen (14,53,(71)(72)(73). Previous studies have shown the in vivo expression of both proteins by M. leprae (62,71).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hlp and HBHA are well known as extracellular matrixbinding proteins. While HBHA binds heparan sulfate (13,20), Hlp has been described as a multifunctional adhesin able to interact with laminin, hyaluronic acid, heparan sulfate, and collagen (14,53,(71)(72)(73). Previous studies have shown the in vivo expression of both proteins by M. leprae (62,71).…”
Section: Discussionmentioning
confidence: 99%
“…leprae Hlp and HBHA can mediate mycobacterial entry into epithelial cells. Two mycobacterial proteins, HBHA and Hlp, have been intensely studied and shown to mediate bacterial adhesion to epithelial cells (13,20,53). Since we confirmed by proteomic data that HBHA and Hlp are surface-exposed proteins in M. leprae, we investigated whether recombinant M. leprae proteins would be able to bind to A549 and RPMI 2650 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the TadA homolog HbhA is found in both pathogenic and nonpathogenic mycobacteria and has previously been shown to act as a virulence factor in Mycobacterium tuberculosis and Mycobacterium leprae, for which it is believed to promote dissemination during early stages of infection (13,30). Interestingly, M. tuberculosis has been shown to accumulate TAG and store it in conspicuous inclusion bodies, similar to those seen for Rhodococcus (12,19,20).…”
Section: Vol 76 2010mentioning
confidence: 96%
“…For infectious bacteria, surface proteins are essential components of many aspects of pathogenesis (47,48). Host specificity, adhesion, invasion, molecular transport, and antimicrobial resistance are processes known to be directly mediated by proteins present at the surface interface (16,17,50,81). These proteins are also the primary target of the host immune system.…”
mentioning
confidence: 99%